A Survey of US Travelers to Asia to Assess Compliance With Recommendations for the Use of Japanese Encephalitis Vaccine. Issue 3 (8th March 2013) - Duffy, Mark R.; Reed, Christie; Edelson, Paul J.; Blumensaadt, Sena; Crocker, Kimberly; Griggs, Anne; Biggerstaff, Brad J.; Delorey, Mark J.; Hayes, Edward B.; Fischer, Marc
Abstract : Background: Japanese encephalitis (JE) vaccine is recommended for travelers to Asia whose itineraries increase their risk of exposure to JE virus. The numbers of travelers with such itineraries and the proportion of those who receive JE vaccine are unknown. We performed a survey to estimate the proportion of US travelers to Asia who receive JE vaccine according to the Advisory Committee on Immunization Practices (ACIP) recommendations. Methods: We surveyed US residents ≥18 years old departing on 38 flights to Asia selected through a stratified random sample of all direct flights to JE‐endemic countries from three US airports. We asked participants about planned itineraries and activities, sources of travel health information, JE vaccination status, and potential barriers to vaccination. Participants planning to spend ≥30 days in Asia or at least half of their time in rural areas were defined as "higher JE risk" travelers for whom vaccination should have been considered. Results: Of 2, 341 eligible travelers contacted, 1, 691(72%) completed the survey. Among these 1, 691 participants, 415 (25%) described itineraries for which JE vaccination should have been considered. Of these 415 higher JE risk travelers, only 47 (11%) reported receiving ≥1 dose of JE vaccine. Of the 164 unvaccinated higher JE risk travelers who visited a health care provider before their trip, 113 (69%) indicated that they had never heard of JE vaccine or their health care provider had not offered or recommended JE vaccine. Conclusions: A quarter of surveyed US travelers to Asia reported planned itineraries for which JE vaccination should have been considered. However, few of these at‐risk travelers received JE vaccine.